Prevalence of SARS-CoV-2 infection among health care workers in a reference hospital in Brazil - Almeida, Vanessa Neves (2023)
Health care workers (HCW) are the frontline workforce for COVID-19 patient care and, consequently, are exposed to SARS-CoV-2 infection due to close contact to infected patients. Here, we evaluate the prevalence of SARS-CoV-2 infection among HCW from an infectious disease hospital, reference center for COVID-19 care in the metropolitan area of Sao Paulo city, Brazil. Among 2,204 HCW, 1,417 (64.29%) were subjected to detection of anti-SARS-CoV-2 antibodies by chemiluminescent immunoassay. Out of the total, 271 (19.12%) presented anti-SARS-CoV-2 antibodies. Prevalence varied according to HCW categories. The highest prevalence was observed in workers from outsourced companies, cooks and kitchen assistants, hospital cleaning workers, and maintenance workers. On the other hand, resident physicians and HCW from the institution itself presented lower prevalence (nurses, nursing assistants, physicians, laboratory technicians). Social and environmental factors are important determinants, associated with exposure in the hospital environment, which can determine the greater or lesser risk of infection by pathogens that spread rapidly by air.